(untitled) (Research, Society and Development, 2020)
Crystallization of lactose in a vibrated bed is a good alternative for obtaining lactose with greater uniformity and yield compared to conventional crystallizers. A central composite design was proposed to verify the significant variables of the operation, analysis of the response surfaces and technical optimization of the process. The maximum yield achieved in design with commercial seeds was 126%, which resulted in the largest final diameter of 4.8 × 10-6 m. There is a great influence of supersaturation and operating time on the mass yield and product size. In optimization, the predicted conditions as the maximum response generators indicated responses of 138% and 4.8 × 10-6 m which, when tested experimentally, resulted in responses of 138.96 ± 3.22% for the yield and 4.777 ± 0.092 × 10-6 m for the final average diameter, with deviations from the predicted values of 0.85% and 0.86%, respectively. A decrease in the mean size of the crystals was observed, in relation to the average size of the seeds inserted at the beginning of the crystallization, which may be related to the configuration of the seeds used, which present microparticles adhered to the surface of the crushed crystals, generating new crystallization nuclei and wear or detachment of portions of fractured seeds at the time of grinding.